Project-based teaching-learning computer-aided engineering tools - Simões, J.A.
Computer-aided design, computer-aided manufacturing, computer-aided analysis, reverse engineering and rapid prototyping are tools that play an important key role within product design. These are areas of technical knowledge that must be part of engineering and industrial design courses’ curricula. This paper describes our teaching experience of computer-aided tools for product design centred on the development of a proposed project. The pedagogic model, the teaching objectives and methodology are described and discussed. The competencies acquired within the development of the project have stimulated the design and manufacturing of several artefacts within the students’ final-year project. A conceptual vehicle, a washing machine and a tricycle were products designed by students and are presented.